Competency Management, Coordination and Responsibility in Slovenia - Zupančič, Magda (Naše gospodarstvo/Our economy, 2020)
The purpose of this article is to highlight the importance of investments into competencies. The identification of competencies should belong to the strategic goals of any socially responsible society. The right competencies are a crucial precondition for a functioning labour market in times of digitalisation and technological changes: for good economic performance as well as to ensure lifelong productive and inclusive individuals. Relevant skills and competencies should respond to labour market needs as well as to economic requirements. The approach to this study is linked to the practical deficiencies of ineffective competency management in Slovenia and its consequences. The methodology combines study of theoretical models and specific skill framework in selected countries with chosen policies. The findings confirm that educational paths in Slovenia are not aligned with the economy requirements. Competencies do not correspond to actual industrial policy priorities. The article identifies the reality of competency policy in Slovenia and governance gaps in comparison with EU and OECD countries. It focuses on foreseen skills challenges and skills forecasting needs. The article offers solutions and policies for better skills matching and further reflections on more co-ordination and governance between educational policies and competency requirements in the economy. One limitation of this study is the variety of policies in countries, hindering the transferability. Nevertheless, the article tackles skill and competency challenges, which are common in most of the countries and require actions.